If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=-3F^2+75
We move all terms to the left:
(F)-(-3F^2+75)=0
We get rid of parentheses
3F^2+F-75=0
a = 3; b = 1; c = -75;
Δ = b2-4ac
Δ = 12-4·3·(-75)
Δ = 901
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(1)-\sqrt{901}}{2*3}=\frac{-1-\sqrt{901}}{6} $$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(1)+\sqrt{901}}{2*3}=\frac{-1+\sqrt{901}}{6} $
| d+35-35=120-35 | | n=52n+5 | | 3x-(x+5)=-10x+2x+5 | | -6(5x+3)=12 | | 1/10y+3=-8 | | 3x-(x+5)=-10+2x+5 | | 7(y-5)=-35 | | -16=y-16 | | 2(3x−5)=7x+4 | | T=5s+4.86 | | 9-4x=6x-17 | | -112=7(3x+5) | | 2x*3=1x+13 | | 5n+8=9n | | 6xW=42 | | 6y=90×= | | 7+8=m-5 | | 10x2(x+8)+1=0 | | 9-3x-2x2=0 | | 5(x+3)=7x=33 | | 8x-5=4-x+7 | | 6v-8+2v=3(3v-2)+2(-2v+4) | | 180=(7x-4)+132 | | x+5+x=45 | | 3x-21+15= | | -7(2x-8)-7=7(4+x) | | 2-x-x2=0 | | 9x-5(3x-12)=-24 | | -3x+8×10x-2=2x-14 | | -6+2v=6v+6 | | -20+4w=200 | | 486.34=240+1.23x |